TOP MANAGEMENT RESPONSIBILITIES IN STRATEGIC MANAGEMENT OF STUDENT ACHIEVEMENT AT MTSN 8 KEDIRI - Laily Faridhatun Nikmah; Sulistitorini; Agus Zaenul Fitri (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2024)
Education is very important in everyday life, but the quality of education in Indonesia is still low for various reasons. These include a lack of sense of urgency, falling behind the curriculum, and a lack of appropriate learning. Education is a very important skill for everyone. Good education depends note only on individual abilities but also on a good education system and effective management. A good education can also help people achieve goals such as as getting a higher level of education, getting a suitable job, and advancing their careers. Therefore, the aim of this research is to analyze effective strategic management for improving strong education. This research uses qualitative as a research method. And this is also done through collecting data from various sources, such as journals, books and articles. The results of this research show that the responsibility of top management in effective strategic management is formulating vision and mission, formulating strategies, implementing strategies and evaluating strategies and has several factors that influence increasing student achievement, including creating a sense of urgency, using curriculum and programs that new, setting bold and ambitious goals, using new student admission selection, providing appropriate learning, providing extra time and assistance to students who experience difficulties and teachers as role models. The conclusion can be drawn that strategic management requires environmental analysis, strategy formulation, strategy implementation and evaluation and control.